Implicações jurídico-ambientais decorrentes da exploração econômica dos recursos genéticos da biodiversidade brasileira e dos conhecimentos tradicionais associados à ela - Guilherme, Fabiane Marisa Salvajoli (2016)
The transformations that have occurred in recent times resulting from scientific and technological advances have sued the use and exploitation of biodiversity resources for their realisation. Notice that the biodiversity-rich countries and poor in technology ended up being harmed in these business relationships, even if they are holders of the raw material (genetic resources), behold the genetic heritage, until then, was regarded as the common heritage of mankind. With the advent of the Convention on biological diversity these resources began to be regulated by the legislation of the country in which they are inserted, especially with regard to access and the sharing of the benefits arising from the use of these. In Brazil, such as legal framework, we had the provisional measure no. 2.186-16/2001 which ran for over fourteen years, showing positive and negative aspects, and so currently replaced by the Biodiversity Act, law No. 13.123/2015. The need for a new Bill.